«It is not the Legs that Win a Football Game, but the Head»: Football Thematics and its Reflection in the Articles on Sports by Taras Franko (Linguostylistic Studies, 2019)
The article considers the key issues of the formation and development of Ukrainian football discourse in the first half of ХХ century in Halychyna. The study has been performed on the basis of sports articles about football by Taras Franko. The author suggests classification of the Ukrainian football vocabulary / lexicon revealed in T. Franko’s publications about football. In the focus of attention are the vocabulary scope of each of the selected thematic groups and the lexemes use frequency, first of all in those cases when there are several competitive alternative terms for defining special football concepts and notions. The study has revealed that Taras Franko in his articles about football uses lexical units from all the most important thematic groups dealing with variations of the football terms and nominations denoting: a football game; football matches and the participants; a football field, its parts, layout and facilities; names of football players and judges’ actions; elements of a game; kicks of the ball; tactical schemes; rules violation; the results of a match and training processes. Being an author of remarkable fundamental works on history and theory of football Taras Franko contributed much to the development of national football discourse in the first half of ХХ century.
Keywords: Taras Franko; a sports article about football; Ukrainian football vocabulary; a special notion in the domain of football; national football discourse